2010
DOI: 10.1007/s10567-010-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Feeding Disorders: A Quantitative Synthesis of Treatment Outcomes

Abstract: A systematic review of the literature regarding treatment of pediatric feeding disorders was conducted. Articles in peer-reviewed scientific journals (1970-2010) evaluating treatment of severe food refusal or selectivity were identified. Studies demonstrating strict experimental control were selected and analyzed. Forty-eight single-case research studies reporting outcomes for 96 participants were included in the review. Most children presented with complex medical and developmental concerns and were treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
168
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(176 citation statements)
references
References 93 publications
7
168
0
1
Order By: Relevance
“…Regardless of the epidemiology of the feeding disorder, previous research has shown that a behavior analytic approach to assessment and treatment is effective in increasing consumption and reducing refusal (Piazza, 2008). Sharp, Jaquess, Morton, and Herzinger (2010), in a review of 48 studies involving the treatment of pediatric feeding disorders, found that each underscored the use of a behavioral intervention. Consequences, such as the delivery of attention, provided by caregivers following food refusal, or inappropriate mealtime behavior (IMB), during and surrounding mealtimes have been shown to reinforce IMB and result in its maintenance.…”
mentioning
confidence: 99%
“…Regardless of the epidemiology of the feeding disorder, previous research has shown that a behavior analytic approach to assessment and treatment is effective in increasing consumption and reducing refusal (Piazza, 2008). Sharp, Jaquess, Morton, and Herzinger (2010), in a review of 48 studies involving the treatment of pediatric feeding disorders, found that each underscored the use of a behavioral intervention. Consequences, such as the delivery of attention, provided by caregivers following food refusal, or inappropriate mealtime behavior (IMB), during and surrounding mealtimes have been shown to reinforce IMB and result in its maintenance.…”
mentioning
confidence: 99%
“…4 A recent meta-analysis indicated that children with ASD are four times more likely to have eating problems compared to their peers with typical development (odds ratio [OR] = 5.11; 95% confidence interval [95%CI] 3.74-6.97). 8 All the above-mentioned studies dealt with eating problems in patients with ASD from the perspective of the healthcare professional/ physician, with no information on the perceptions and concerns of parents in relation to the eating habits of individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of problems may range from 13 to 50% in typically developing children, but may be as high as 80% in children with developmental disabilities [1][2][3][4][5][6][7]. In 1 to 10% of these children problems may become chronic and may affect their health and development [1,8]. Anatomical, metabolic, gastrointestinal, motor or sensory problems may be the cause of or may contribute to some of these feeding problems [8].…”
Section: Introductionmentioning
confidence: 99%